Graphiola Leaf Spot (False Smut) of Palm - Monica L. Elliott (EDIS)
Graphiola leaf spot, also referred to as “false smut,” is a foliar pathogen of certain palm species. In Florida, it is primarily a cosmetic disease and does not adversely affect plant growth. Nutrient deficiencies, such as potassium or magnesium deficiency, are much more serious palm health problems than this disease, especially for Phoenix palm species. This document is PP-216, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date January 2006.